"Alien hand" and loss of bimanual coordination after dominant anterior cerebral artery territory infarction. Issue 2 (February 1988) - McNabb, A W; Carroll, W M; Mastaglia, F L
Abstract : Three patients with dominant anterior cerebral artery territory infarction demonstrated a severe disturbance of upper limb motor control with impaired bimanual coordination, the "alien hand" sign, and intermanual conflict, in addition to signs of callosal interruption and a transcortical motor aphasia. Recordings of movement-related potentials in one patient showed an attenuated Bereitschaftspotential and a greater asymmetry of the NS' component of the premotor negativity with left finger than with right finger movement. The impairment of bimanual motor control and associated abnormal motor behaviour of the right hand in these cases are postulated to be due to involvement of the supplementary motor area and related areas of the medial frontal cortex.